DISKUSI NASKH DALAM WACANA STUDI AL QUR’AN - Supriyanto, John (STIQ Al-Lathifiyyah Palembang, 2019)
This paper decribes the existence of the Qur?an abrogation or it?s popularly called the naskh of Qur?an which was introduced by the ?ulama? in early days of growth and development of Qur?an sciences. The study of abrogation in the Qur?an as part of tehe study ?Ulum al-Qur?an is still questionable until now. It can be proved tha there are a lot of ulama who oppose the theory of naskh by reducing the verses of Qur?an which are considered have been abrogated. Thus, from time to time the number of abrogation verses is decreasing. Nevertheless, this theme is still warm to be discussed especially when the position of the Qur?an as a holy text that has undergone a transformation and as a culture product.